MCSE guide to managing a microsoft windows server 2003 environment - DiNicolo, Dan (Thomson Course Technology, 2004)
This hands-on guidebook is designed to prepare students for the MCSE certification exam and for the challenges they will face as Microsoft networking professionals. Projects and exercises reinforce skills as they are learned and extensive test preparation resources help students get ready for exam day. Includes 180-day Trial Version of Microsoft Windows Server 2003. Maps completely to the objectives for MCSE Exam #70-290. Updated to include the CoursePrep ExamGuide workbook containing key information and review questions for every exam objective. Reinforces skills as they are learned with extensive Review Questions, hands-on Activities, and Case Projects in each chapter. Includes free CertBlaster and CoursePrep test preparation software on CD-ROM to help students practice for exam day.